Giving back: women's entrepreneurial philanthropy - Oppedisano, Jeannette (Women in Management Review, 2004)
Traditionally, the concept of entrepreneurship included a for-profit bottom line. Recently, however, researchers have begun to explore an adaptation of this model called “social entrepreneurship”; that is, creating organizations for the greater good of a community, region, nation, or the world. These entrepreneurs use money that they made or inherited to establish organizations from a missionary and visionary posture. This is an arena where women have had significant impact, yet little has been written to celebrate their contributions. The purpose of this paper is to explore the concept of such philanthropy, to suggest where this social ethic might have had its origins, and to provide samples of women who have been entrepreneurial in their social commitment. Suggestions for future research on women's entrepreneurial philanthropy will also be made. © 2004, Emerald Group Publishing Limited
Keywords: Entrepreneurialism; Philanthropy; Social action; United States of America; Women; dept.mgt